PENINGKATAN MINAT SUMBER DAYA MANUSIA PENGELOLAAN SAMPAH DI BANK SAMPAH KAPPSA DESA CIMEKAR - Wahyuni, Sri (Jurnal Abdimas Sang Buana, 2024)
Waste management is a significant issue faced by the community in Cimekar Village, particularly in the KAPPSA  Waste Bank. One of the primary challenges in waste management is the low interest and participation of human resources in managing waste. This Community Service Program aims to identify the obstacles in increasing human resource engagement in waste management at the KAPPSA Waste Bank.The method employed in this study is qualitative, utilizing a case study approach that involves in-depth interviews and participant observation. The findings reveal that a lack of understanding about the importance of waste management, limited resources, and low environmental awareness are the main factors hindering public interest. Additionally, social and economic factors contribute to the decline in community participation in waste management activities.In conclusion, more effective strategies are needed, such as enhancing environmental education, empowering the community, and fostering collaboration with various stakeholders, to address these challenges and boost community interest in waste management at the KAPPSA  Waste Bank in Cimekar Village. It is hoped that these programs will encourage active community involvement in maintaining environmental cleanliness and sustainability